Characteristics of growth, flowering and corm yield of iles-iles (Amorphophallus muelleri) genotypes at third growing period - MOHAMMAD TAJUDDIN; edi Santosa; DIDY SOPANDIE; ADOLF PIETER LONTOH (Society for Indonesian Biodiversity, 2020)
Abstract. Tajuddin M, Santosa E, Sopandie D, Lontoh AP. 2020. Characteristics of growth, flowering and corm yield of iles-iles (Amorphophallus muelleri) genotypes in third growing period. Biodiversitas 21: 570-577. Iles-iles (Amorphophallus muelleri Blume) is an emerging crop for producing glucomannan, and it is predominantly cultivated in agroforestry systems. The study aimed to evaluate characteristics of growth, flowering, and production of genotypes in the third growing period in order to develop new clones. The experiment used 2-year-old corm of ten genotypes, i.e. BKB, CF, CR, LSP, SB, SBM, SG-BKK, SGH, SR and STS. The corms were planted in June 2018 to May 2019 in the field under 45% artificial shading net. Plant growth was evaluated on weekly basis from bud emergence until dormant. Flowering rate was ratio the number of corms with flower to number of planted corms in each replication. Corm dry mass was measured after harvest, which was conducted at dormant stage at 46 weeks after planting. Candidate clone was selected from the highest total score of five criteria i.e. flowering rate, corm shape, corm healthiness, marketable yield, and total yield. Results demonstrated that genotypes exhibited variation in growth, flowering rates, and yield. Based on emerging time, three genotypes (SB, SGH, SG-BKK) were classified as early emergence, five genotypes (CF, CR, LSP, SBM, STS) as a medium, and two genotypes (BKB, SR) as the late emergence. All genotypes produced inflorescence at rate 1 to 52%, and 3 genotypes (CF, CR, STS) had flowering rate >20%. Five genotypes (CR, LSP, SBM, SGH, STS) had an average corm weight > 1500 g. CR and SBM genotypes produced the largest average corm weight, i.e., 2,509.33 g and 2,129.25 g, respectively, while the BKB produced the smallest one (912.94 g). All genotypes had similar dry mass content, i.e., 18.73-20.70%. The scoring evaluation recommended CR, SBM, and STS genotypes as candidates of new clones with productivity > 30 ton/ha. It needs further evaluation of selected clones in the farmer production field.